Evaluation of IS project success in InfSysMakers: an exploratory case study - Varajão, João (2016)
Evaluating the success of information systems projects is a key process in project management. Even though many studies found in literature focus on various aspects of project success like, for example, the success factors, there are few studies that address the evaluation process and that present practical cases. In order to help fill this gap, this paper presents an exploratory case study of a company called InfSysMakers (anonymized company name), aiming to get answers to the following questions "How is the process for evaluating the success of projects defined?"; "What criteria are used to evaluate the project success?"; "When does the evaluation actions take place to measure success?"; "Who are the stakeholders that participate in the evaluation?" Based on the obtained results, we propose a preliminary model for assessing the success of projects. The results are useful for researchers and practitioners interested in improving the project success evaluation process